Differences in Functional Brain Connectivity Alterations Associated with Cerebral Amyloid Deposition in Amnestic Mild Cognitive Impairment - Yi, Dahyun; Choe, Young Min; Byun, Min Soo; Sohn, Bo Kyung; Seo, Eun Hyun; Han, Jiyoung; Park, Jinsick; Woo, Jong Inn; Lee, Dong Young (Frontiers in Aging Neuroscience, 2015)
Despite potential implications for the early detection of impending AD, very little is known about the differences of large scale brain networks between amnestic MCI (aMCI) with high cerebral amyloid beta protein (Aβ) deposition (i.e., aMCI+) and aMCI with no or very little Aβ deposition (i.e., aMCI-). We first aimed to extend the current literature on altering intrinsic functional connectivity (FC) of the default mode network (DMN) and salience network (SN) from CN to AD dementia. Second, we further examined the differences of the DMN and the SN between aMCI-, aMCI+, and CN. Forty-three older adult (12 CN, 10 aMCI+, 10 aMCI-, and 11 AD dementia) subjects were included. All participants received clinical and neuropsychological assessment, resting state functional MRI, structural MRI, and Pittsburgh compound-B-PET scans. FC data were preprocessed using Multivariate Exploratory Linear Optimized Decomposition into Independent Components of FSL. Group comparisons were carried out using the “dual-regression” approach. In addition, to verify presence of grey matter (GM) volume changes with intrinsic functional network alterations, Voxel Based Morphometry was performed on the acquired T1-weighted data. As expected, AD dementia participants exhibited decreased FC in the DMN compared to CN (in precuneus and cingulate gyrus). The degree of alteration in the DMN in aMCI+ compared to CN was intermediate to that of AD. In contrast, aMCI- exhibited increased FC in the DMN compared to CN (in precuneus) as well as aMCI+. In terms of the SN, aMCI- exhibited decreased FC compared to both CN and aMCI+ particularly in the inferior frontal gyrus. FC within the SN in aMCI+ and AD did not differ from CN. Compared to CN, aMCI- showed atrophy in bilateral superior temporal gyri whereas aMCI+ showed atrophy in right precuneus. The results indicate that despite of the similarity in cross-sectional cognitive features aMCI- has quite different functional brain connectivity compared to aMCI+.